Nanostructured Few-Layer Graphene with Superior Optical Limiting Properties Fabricated by a Catalytic Steam Etching Process - Sun, Zhenyu (2013)
Tailoring the morphology and structure of graphene can result in novel properties for advanced applications. Here, we demonstrate the fabrication of nanostructured few-layer graphene through a mild etching process via catalytic steam gasification of carbon by Fe nanoparticles (NPs). Controlling the reaction temperature, steam concentration, and the loading density of the NPs enables the finetuning of the etching level of graphene. Well-defined nanotrenches with a width of less than 25 nm were formed by channeling of the catalytic NPs. Etching caves and  quasisemicircular etched edges were observed as well. The nonlinear optical properties of the resulting nanostructured graphene were studied under a 532 nm nanosecond pulse laser through an open-aperture apparatus. At the same level of the linear extinction coefficient, it exhibits superior optical limiting performance in comparison with pristine graphene and C60, showing a large potential in nanophotonic devices. This enhancement is ascribed to the defects formed by etching resulting in a finite band gap in nanostructured graphene.